2008
DOI: 10.1111/j.0906-7590.2008.05206.x
|View full text |Cite
|
Sign up to set email alerts
|

Postglacial dispersal limitation of widespread forest plant species in nemoral Europe

Abstract: Climate is often singled out as the primary range limiting factor at large scales, while other environmental factors, notably soil, are thought to predominate at smaller scales. However, the postglacial migrational lag hypothesis controversially suggests that many species are strongly dispersal-limited and still expanding from their ice age refugia. We investigated the importance of postglacial migrational lag, climate, and soil as range determinants for 47 widespread forest plant species across nemoral Europe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
248
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 229 publications
(266 citation statements)
references
References 50 publications
16
248
2
Order By: Relevance
“…The assumption of equilibrium between a species distribution and environmental conditions is less valid in disturbed ecosystems such as Mediterranean forests, where human influence is strong (e.g., land-use effects, fire occurrences). It has also been reported that many European tree species are not in equilibrium with climate , not P. sylvestris, which was reported to be in relative equilibrium) as a consequence of postglacial dispersal limitations (Svenning et al, 2008). In this study, some of the observed imbalance between environment and spatial aggregation of tree species might be explained by the lack of equilibrium between species and current environmental conditions.…”
Section: Discussionmentioning
confidence: 48%
“…The assumption of equilibrium between a species distribution and environmental conditions is less valid in disturbed ecosystems such as Mediterranean forests, where human influence is strong (e.g., land-use effects, fire occurrences). It has also been reported that many European tree species are not in equilibrium with climate , not P. sylvestris, which was reported to be in relative equilibrium) as a consequence of postglacial dispersal limitations (Svenning et al, 2008). In this study, some of the observed imbalance between environment and spatial aggregation of tree species might be explained by the lack of equilibrium between species and current environmental conditions.…”
Section: Discussionmentioning
confidence: 48%
“…However, a species' ability to respond is affected by local geomorphic processes (Macias-Fauria and Johnson 2013), grazing (Speed et al 2012) and community interactions such as dense grassland (Rehm and Feeley 2015). Based on the predicted required shifts, it seems that the species will not be able to track the projected warming which may cause them to lose their potential habitat (Engler et al 2011;Svenning et al 2008) and reduce their population size (Feeley and Silman 2010).…”
Section: Discussionmentioning
confidence: 99%
“…[7,8]), as well as from species distribution modelling (SDM) (e.g. [9]). Indeed, these pieces of evidence support the existence of glacial refugia (sensu [10]) in higher latitudes for some temperate and boreal species.…”
Section: Introductionmentioning
confidence: 99%